Developing teacher leaders in special education an administrator's guide to building inclusive schools - Maggin, Daniel Montagne; Tejero Hughes, Marie 1965- (Routledge eye on education, 2021)
"Practical and forward-thinking, Developing Teacher Leaders in Special Education is the administrator's essential guide to growing special educator leadership in any school, district or program. Special educators need to be flexible, proactive, and collaborative - qualities that make them uniquely suited to roles in school leadership - but these skills are often overlooked when choosing effective teacher leaders. Featuring helpful tips and detailed examples to demonstrate the concepts in action, this book breaks down the qualities that special educators can bring to your school leadership team and explores how you can leverage those skills to create a more inclusive and successful community"--